2022
DOI: 10.3389/fmed.2022.952636
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of metagenomic next-generation sequencing for detecting pathogens in bronchoalveolar lavage fluid collected from children with community-acquired pneumonia

Abstract: This study is to evaluate the usefulness of pathogen detection using metagenomic next-generation sequencing (mNGS) on bronchoalveolar lavage fluid (BALF) specimens from children with community-acquired pneumonia (CAP). We retrospectively collected BALF specimens from 121 children with CAP at Tianjin Children's Hospital from February 2021 to December 2021. The diagnostic performances of mNGS and conventional tests (CT) (culture and targeted polymerase chain reaction tests) were compared, using composite diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 39 publications
1
19
1
Order By: Relevance
“…An alternative rapid diagnostic method is next-generation metagenomic sequencing (NGS), which has the advantage of being unrestricted in the potential pathogens it may detect. Paediatric studies of NGS describe it as a sensitive test, but it is difficult to determine its clinical application given that studies tend to report positive detection rates in comparison with culture rather than sensitivity and specificity [ 28 30 ]. The relevance of low prevalence pathogens and fluctuations in the composition of the respiratory microbiome remains a challenge for the interpretation of molecular diagnostics [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…An alternative rapid diagnostic method is next-generation metagenomic sequencing (NGS), which has the advantage of being unrestricted in the potential pathogens it may detect. Paediatric studies of NGS describe it as a sensitive test, but it is difficult to determine its clinical application given that studies tend to report positive detection rates in comparison with culture rather than sensitivity and specificity [ 28 30 ]. The relevance of low prevalence pathogens and fluctuations in the composition of the respiratory microbiome remains a challenge for the interpretation of molecular diagnostics [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in southern China, the detection rates of M. pneumoniae using nasopharyngeal swabs of inpatients with acute respiratory infection were also unprecedentedly reduced from 20% in 2019 to 1.0% in 2020[7]. However, another study using BALF from a city in northern China, showed that M. pneumoniae was the most frequently detected pathogen, at a rate of up to 73.55%[24]. Furthermore, the detection of M. pneumoniae further increased despite the NPIs that were adopted during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the impact of the COVID-19 pandemic on the pathogen spectrum of respiratory tract infections in children[5-7,24], but the corresponding differences in clinical manifestations have rarely been studied. During the COVID-19 pandemic, we found a decreased proportion of rhonchi, chest indrawing, bilateral lung infiltrates and bronchial lumen morphological changes, but a significantly higher proportion of decreased breath sounds, rales, consolidation, unilateral lung infiltrates and bronchial mucus plugs.…”
Section: Discussionmentioning
confidence: 99%
“…We have done mNGS studies of bronchoalveolar lavage fluid with community-acquired pneumonia, and found that the positive coincidence rate of the mNGS method for pathogens was much higher than that of the CT method (culture and targeted polymerase chain reaction tests). 5 However, further studies are needed for severe pneumonia. This study aimed to investigate the significance of mNGS examination of alveolar lavage fluid in children with severe pneumonia.…”
Section: Introductionmentioning
confidence: 99%